BACI monitoring of effects of hydraulic dredging for cockles on intertidal benthic habitats of Dundalk Bay, Ireland. (16th June 2014) - Clarke, Sarah; Tully, Oliver
Abstract : Hydraulic dredging for bivalves, such as cockles ( Cerastoderma edule ), has the potential to cause significant impacts on marine intertidal benthos. Although this fishing activity is common in northern European Natura 2000 sites such impacts may be incompatible with conservation objectives for designated habitats and species within these sites. In 2009–2010 a spatially nested control-impact study was undertaken before ( t 0 ), 8–9 days after ( t 1 ) and 4 months ( t 2 ) following dredging and extraction of 108 tonnes of cockles from a standing stock of 2158 tonnes in Dundalk Bay. This study failed to detect significant effects on benthic sediments, or the overall community structure. However, a fishing effect on the target species C. edule in one sampling area and a short lived effect on the bivalve Angulus tenuis were identified. Significant spatial and temporal variability in abundance of species and taxonomic groups, unrelated to fishing effects, was observed. Previous studies on the effects of fisheries on marine intertidal benthos have reported variable results, related to study design and objectives and the physical characteristics of the study site. Site specific studies, relative to the intensity and frequency of proposed fishing activity, may be required to adequately inform managers whether such activities are compatible with specific conservation objectives for Natura 2000 sites.